Richness, distribution and important areas to preserve Bulbophyllum in the Neotropics - Smidt, Eric (Universidad de Costa Rica, 2015)
Bulbophyllum is probably one of the largest genera in the orchids with Pantropical occurence, but the dis- tribution is not homogeneous across the world. The Paleotropics is the richest area and there are hundreds of species in Asia (Vermeulen 1991). The genus was described by Thouars in 1822, and the first Neotropical species was described only in 1838 (B. setigerum Lindl.) from a plant collected in Guayana by George Loddiges and sent to John Lindley. Until today, one hundred and ten species names were pub- lished for the Neotropics, however only ca. 70 species could be recognized in five sections supported by phy- logenetic studies based on nuclear and chloroplast genome sequence data (Smidt unpubl. data).